2010
DOI: 10.1371/journal.pone.0010613
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, Robust and Scalable Patterns Underlie Human Approach and Avoidance

Abstract: BackgroundApproach and avoidance behavior provide a means for assessing the rewarding or aversive value of stimuli, and can be quantified by a keypress procedure whereby subjects work to increase (approach), decrease (avoid), or do nothing about time of exposure to a rewarding/aversive stimulus. To investigate whether approach/avoidance behavior might be governed by quantitative principles that meet engineering criteria for lawfulness and that encode known features of reward/aversion function, we evaluated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(112 citation statements)
references
References 135 publications
4
108
0
Order By: Relevance
“…It can be assumed that the conditioned incentive properties of the partner, hence the response of approach, had reached an asymptotic level by Day 6. Any further increase in response intensity would be offset because of habituation (McSweeney & Murphy, 2009; Carr & Epstein, 2011) or because of negative alliesthesia (Cabanac, 1971; Brondel et al, 2009; Kim et al, 2010). Thus, performance of conditioned responses stabilizes or gets reduced, as is the case with some sociosexual behaviors in long term marmoset pairs (see Introduction) and in human long term relationships (Klusmann, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the conditioned incentive properties of the partner, hence the response of approach, had reached an asymptotic level by Day 6. Any further increase in response intensity would be offset because of habituation (McSweeney & Murphy, 2009; Carr & Epstein, 2011) or because of negative alliesthesia (Cabanac, 1971; Brondel et al, 2009; Kim et al, 2010). Thus, performance of conditioned responses stabilizes or gets reduced, as is the case with some sociosexual behaviors in long term marmoset pairs (see Introduction) and in human long term relationships (Klusmann, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Third, our stimuli were not matched on pleasantness (see Appendix 1, "Stimuli" sec tion, for more details) and were not assessed on other dimensions, including arousal, dominance, 58 or effort ex penditure to view. 59 Finally, the limited number of brain regions of interest (i.e., NAcc and mOFC), the focus on the session × stimulus interaction instead of pairwise compari son between sessions across stimulus categories, and a rel atively small sample size may have limited our ability to fully unravel the effects of XRNTX on brain function (e.g., neural responses to sexual and aversive stimuli). It is our hope that our study sets the stage for filling these gaps in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Our prior work has shown that both frameworks appear to work well within the range of interpretable human keypressing (Breiter and Kim, 2008; Kim et al, 2010; Lee et al, 2015). In this manuscript, we addressed this question by comparing the R 2 values for the approach and avoidance curves between the logarithmic and power-law fits, in order to see whether one of the functions had significantly higher goodness of fit values.…”
Section: Resultsmentioning
confidence: 93%